Genotoxicity of multi-walled carbon nanotubes at occupationally relevant doses - Siegrist, Katelyn J (BioMed Central, 2014)
Carbon nanotubes are commercially-important products of nanotechnology; however, their low density and small size makes carbon nanotube respiratory exposures likely during their production or processing. We have previously shown mitotic spindle aberrations in cultured primary and immortalized human airway epithelial cells exposed to single-walled carbon nanotubes (SWCNT). In this study, we examined whether multi-walled carbon nanotubes (MWCNT) cause mitotic spindle damage in cultured cells at doses equivalent to 34 years of exposure at the NIOSH Recommended Exposure Limit (REL). MWCNT induced a dose responsive increase in disrupted centrosomes, abnormal mitotic spindles and aneuploid chromosome number 24 hours after exposure to 0.024, 0.24, 2.4 and 24 μg/cm(2) MWCNT. Monopolar mitotic spindles comprised 95% of disrupted mitoses. Three-dimensional reconstructions of 0.1 μm optical sections showed carbon nanotubes integrated with microtubules, DNA and within the centrosome structure. Cell cycle analysis demonstrated a greater number of cells in S-phase and fewer cells in the G2 phase in MWCNT-treated compared to diluent control, indicating a G1/S block in the cell cycle. The monopolar phenotype of the disrupted mitotic spindles and the G1/S block in the cell cycle is in sharp contrast to the multi-polar spindle and G2 block in the cell cycle previously observed following exposure to SWCNT. One month following exposure to MWCNT there was a dramatic increase in both size and number of colonies compared to diluent control cultures, indicating a potential to pass the genetic damage to daughter cells. Our results demonstrate significant disruption of the mitotic spindle by MWCNT at occupationally relevant exposure levels.